An evaluation of the profile of characteristics of the population of State patients admitted to Valkenberg Hospital's Forensic Unit from December 1964 to May 1997 - Benjamin, Arlene (Department of Psychology, 2017)
Forensic psychiatry is the mental health profession that deals with patients and problems related to both psychiatric and legal services. Due to the dual systems involved, it is not always clear who is serving what sector of the criminal population. Changes in provision of resources calls for ongoing evaluation of the patients being served. Before one can consider the kinds of changes that need to be made in terms of resources one needs to know what the population is. This study provides a profile of the characteristics of State Patients admitted to Valkenberg Hospital's Forensic Unit. The aim is to provide alternatives for the care and treatment of individuals with mental illness who are involved in criminal activity. However, it would appear necessary to explore some of the associated characteristics which have brought these individuals into psychiatric services in the first place. This research, therefore, also explores the relationship that exists between mental disorder and crime in the patients at Valkenberg's forensic unit. The study examines patients admitted to psychiatric hospitals, and for what reasons, as well as what factors contribute to their length of stay or discharge. This relates to the concepts of risk assessment and dangerousness. Patients selected for the research spanned an admission period from 1964 to 1997. The data for the period May 1997-May 1999 was gathered and analysed. Patients admitted to the forensic unit after May 1997 did not qualify for this study as they needed to be in the hospital for at least two years. The patient sample would have been observed and treated for a two-year period. Data was gathered from information recorded in the hospital files. The data was collected using the archival research method. This study gives an account of some of the demographic characteristics of patients admitted to Valkenberg's forensic unit. It was found that a high percentage of patients were charged with physically violent offences and diagnosed as schizophrenic. A high percentage of patients have been detained in hospital for 5 or more years which brings into questions the length of detention of mentally disordered offenders in hospital. A substantial number of patients were found to be apsychotic and mentally stable. However, violent behaviour amongst the patients was prominent. High levels of physical violence in hospital were identified and can be one of the main causes for the ongoing detention of patients in hospital. It remains controversial as to who should be made responsible for managing violent behaviour amongst mentally disordered offenders. It was found that high numbers of patients had been experiencing vacational leave, thereby advancing towards potential for discharge. However, factors such as violent behaviour; problem behaviours e.g. aggression, sexual disinhibition and absconding; substance abuse; and family circumstance may influence the patient's potential for discharge from hospital.